2009
DOI: 10.1128/aem.00628-09
|View full text |Cite
|
Sign up to set email alerts
|

U(VI) Sequestration in Hydroxyapatite Produced by Microbial Glycerol 3-Phosphate Metabolism

Abstract: Previous studies have demonstrated the potential for removal of U(VI) from solution via precipitation of U(VI)-bearing calcium-phosphate (Ca-P) minerals coupled to microbial hydrolysis of glycerol phosphate compounds. We evaluated this process in circumneutral-pH groundwater from Area 2 of the U.S. Department of Energy Field Research Center at Oak Ridge National Laboratory. Area 2 groundwater contains high concentrations of dissolved calcium (ca. 4 mM), and thus, release of phosphate during glycerol phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…However, a major challenge for phosphate-based remediation approaches is the distribution of phosphate in the subsurface; its extremely high reactivity can lead to clogging of the injection well and consequently a limited treatment radius (Wellman et al, 2006). Other researchers have proposed the use of precursor compounds such as glycerol-3-phosphate (Beazley et al, 2007;Shelobolina et al, 2009) or polyphosphate (Wellman et al, 2006) that can be transformed in situ to release phosphate in the subsurface. UFO1 has shown the ability to mediate removal of U(VI) from solution via both bioreduction and phosphate mineral precipitation.…”
Section: Discussionmentioning
confidence: 98%
“…However, a major challenge for phosphate-based remediation approaches is the distribution of phosphate in the subsurface; its extremely high reactivity can lead to clogging of the injection well and consequently a limited treatment radius (Wellman et al, 2006). Other researchers have proposed the use of precursor compounds such as glycerol-3-phosphate (Beazley et al, 2007;Shelobolina et al, 2009) or polyphosphate (Wellman et al, 2006) that can be transformed in situ to release phosphate in the subsurface. UFO1 has shown the ability to mediate removal of U(VI) from solution via both bioreduction and phosphate mineral precipitation.…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, phosphate concentrations are too low in groundwater, and direct phosphate addition to a contaminated aquifer has proven less than effective, as phosphate precipitation near the injection wells prevented distribution/transport of phosphorus source across the subsurface (Wellman et al, 2006). The biomineralization of U(VI) as a result of microbial phosphatase activity is an alternative biologically-induced process by both naturally-occurring and genetically-engineered metal-resistant bacteria that can reduce the solubility of U(VI) by forming uranium phosphate precipitates (Macaskie et al, 1992;Powers et al, 2002;Appukuttan et al, 2006;Martinez et al, 2007;Shelobolina et al, 2009) over a wide pH range . In this process, bacterial phosphatase enzymes hydrolyze phosphate from organophosphate substrates (Macaskie et al, 1994) either to acquire inorganic phosphorus as essential nutrient or to precipitate U(VI) as a detoxification mechanism (Macaskie et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…To further highlight such adaptation, recent investigations of terrestrial and marine bacterial isolates belonging to the genera Aeromonas, Bacillus, Myxococcus, Pantoea, Pseudomonas, Rahnella, and Vibrio demonstrated that Cr, Pb, and U were removed from solution as phosphate minerals under both oxic and anoxic growth conditions [57,60,74,152,[154][155][156][157][158]. Our recent work further examined lead and 6 Advances in Ecology uranium precipitates produced by Rahnella sp.…”
Section: Phosphatase-mediated Biomineralizationmentioning
confidence: 99%
“…Studies examining phosphatase activities (e.g., alkaline or acid) of genetically engineered and naturally occurring strains of Gram-positive and Gram-negative bacteria were shown to promote U immobilization (>90% precipitation of soluble U) via precipitation and coprecipitation reactions [50,57,60,74,[149][150][151][152][153]. Interestingly, soil bacterial isolates demonstrated constitutive phosphatase activities that liberated comparable, if not greater concentrations, of reactive phosphate when compared to the phosphatase activities of genetically modified strains [57,149].…”
Section: Phosphatase-mediated Biomineralizationmentioning
confidence: 99%
See 1 more Smart Citation